2018
DOI: 10.33590/emjdiabet/10312768
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Management of Diabetic Dyslipidaemia

Abstract: Diabetic dyslipidaemia (DD) comprises a complex group of potentially atherogenic lipid and lipoprotein abnormalities, including both quantitative and qualitative changes. It is characterised by low high-density lipoprotein cholesterol, elevated low-density lipoprotein cholesterol (LDL-C), and a higher prevalence of small, dense LDL particles, as well as elevated fasting and postprandial triglycerides. Patients with Type 2 diabetes mellitus have an increased prevalence of lipid abnormalities and controlling dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…The study found that the rates of CVD, all-cause mortality, and CV mortality were significantly higher among adults with diabetes in low-income countries as compared to middle-and high-income countries [8]. Individuals with diabetes have higher cardiovascular risk on comparison with individuals without diabetes [9]. Hence, our study the physicians mentioned risk reduction approach should be focused as a treatment strategy in the centre stage while treating individuals with diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…The study found that the rates of CVD, all-cause mortality, and CV mortality were significantly higher among adults with diabetes in low-income countries as compared to middle-and high-income countries [8]. Individuals with diabetes have higher cardiovascular risk on comparison with individuals without diabetes [9]. Hence, our study the physicians mentioned risk reduction approach should be focused as a treatment strategy in the centre stage while treating individuals with diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…The consequence of high blood pressure on cardio vascular system actually is designated to stress created on vasculature walls, causing aneurisms and brain stroke. Diabetes mellitus and hypertension are considered additive risk escalating factors for CVD (Martín-Timón et al, 2014).…”
Section: A) Modifiable Cardio Vascular Diseases Risk Factorsmentioning
confidence: 99%
“…T2DM is now twice as common in this age group as T1DM in some non-White racial and ethnic groups and has only recently been recognized as a pediatric disease in clinical settings (Perng et al 2023). Diabetes is a complex metabolic disorder characterized by hyperglycemia and problems with insulin production or action, with the potential for developing cardiovascular diseases leading to heart attack and stroke (1985;Martin-Timon et al 2014). While diabetes is one of the major leading causes of death, cardiovascular disease is the main leading cause of death and disability worldwide (Heron 2021).…”
mentioning
confidence: 99%